Effect Processing Lamtoro Leaf (Leucaena leucocephala) As feed on Rex Rabbit Carcass - B Hardiansyah; M Tafsin; A H Daulay; T H Wahyuni; N Ginting (Jurnal Peternakan Integratif, 2017)
This study aims to determine the best treatment of leaf lamtoro so it has not negative impact on the rabbit. Research conducted at the Laboratory of Animal Biology of Animal Husbandry Department on Faculty of Agriculture, University of Sumatera Utara starting from August –October 2016. The design used in this study is completely randomized design (CRD) with 4 treatments and 5 replication. The treatments were utilization of lamtoro leaf treated by drying the sun (P0), oven (700C; 12 hours) (P1), steaming (700C ; 15 minutes + sun drying) (P2) and soaking (12 hours + sun drying) (P3). The parameters studied were slaughter weight, carcass weight, and carcass percentage. The results showed that average slaughter weight (g/head) on treatment P0, P1, P2, P3 were 1562.20, 1576.60, 1413.20, and 1634.00; Carcass weight (g/head) were 780.60, 804.60, 693.40, and 815.60; Carcass percentage (%) were 50.17, 51.00, 48.98, 50.16 respectively. Stastical analysis showed that treatment lamtoro in a pellet ration had no significantly effect (P>0,05) on slaughter weight, and carcass percentage, but the had different effect (P<0.05) on the weight of carcass. The Conclusion of this study is processing lamtoro leaf soaking 12 hours + sun drying, oven 700C; 12 hours, drying the sun aplicable on rabbit diet.